Secret Gardens : Curator : Annemie Van Laethem. - Brans, Louis; Croux, Eric; Késenne, Joannes (Lanaken : Cultureel Centrum, 2001)
Balkenhol, Stephan ; De Bruyckere, Berlinde ; Buggenhout, Peter ; Carlier, Jan ; Daenen, Pie ; Duchateau, Hugo ; Emmerich, Hadassah ; Hoekstra, Berend ; Knippenbergh, Mathieu ; Legrand, Jozef ; Op de Beeck, Hans ; Yufen Qin ; De Roover, Marc ; Somers, Mirjam ; Tahon, Johan ; Vandevelde, Ludwig ; Vanmechelen, Koen ; Visic, Loreta ; Zhou, Shanglie
Nederlands
Secret Gardens. Privé-tuinen en dorp Oud-Rekem, Cultureel Centrum, Lanaken, 27 mei - 17 juni 2001
boek
Keywords: Oud-Rekem